The Canadian Geospatial Data Infrastructure and health mapping - Sheng Gao; Darka Mioc; Xiaolun Yi; François Anton; Eddie Oldfield; David J. Coleman (Cybergeo)
Due to the recent outbreak of SARS and the danger of pandemic Bird Flu, the ability to strengthen health surveillance and disease control is a growing need among governments. The development of the Canadian Geospatial Data Infrastructure (CGDI) has shown great potential in many industries such as emergency management, public health, disaster relief, environmental impact assessment, transportation, and land information systems. In this paper, our aims are to use the CGDI and to identify its usability in supporting online health mapping. To identify the usability of the CGDI for health mapping, we employed nine usability metrics. We also designed an architecture based on the CGDI to support the basic functions for health mapping, and implemented an infectious disease simulation for New Brunswick and Maine. Within the CGDI framework, this research enabled cross-border health data visualization, integration, sharing, and exploring the spatio-temporal trends of an infectious disease outbreak through thematic maps. Based on the experience of the developers and the feedback from users, an evaluation of the usability matrix with the CGDI components (technical standards, national framework data, enabling technologies, and common data policies) was explored using this cross-border health mapping application. The use of the CGDI in health applications has a great potential in supporting effective and secure health data sharing and integration. Enrichment of the CGDI would further facilitate the data sharing and improve decision making efficiency and effectiveness.